Pameran Seni Grafis Borneo 1843 - HERMANU (Bentara Budaya, 2010)
This book review on the island of Borneo or Kalimantan, the largest island duasetelah Irian. One reason for publishing this book is that big island in the past a lot of mystery culture, which until now was still not everything is revealed. The discussion covers the difference between this era with Klaimlantas island state in the 19th century past that still looks beautiful, calm, and peaceful. To commemorate the past Borneo presented in the form of exhibition of the works of graphic works CW Mieling as last year's disclosure Borneo comparison with that in the present situation is very alarming.